Accuracy of numerically evaluated flutter derivatives of bridge deck sections using RANS: Effects on the flutter onset velocity. (15th April 2015) - Patruno, L.
Highlights: The accuracy of bridge deck flutter derivatives estimation using RANS models is discussed. Static aerodynamic coefficients and flutter derivatives are evaluated for 6 decks. Two simulation strategies are compared. The model is tested also for its sensitivity to barriers and average attack angle. Cases in which RANS models are not reliable are found and discussed. Abstract: In this article, the accuracy of standard computational fluid dynamics techniques and turbulence models in predicting the critical flutter speed of streamlined and bluff deck sections is investigated. It is well known that such numerical tools can provide inaccurate prediction of the flow field around bluff bodies which reflects in biases in their aeroelastic behavior. Aiming at systematically study the effects of such inaccuracies, in this article, six deck sections are analyzed by numerically extracting flutter derivatives and calculating the critical flutter speed for a set of representative test structures. It is shown that the flutter onset velocity is mainly underestimated but cases showing opposite behavior are identified and discussed. Two simulation strategies are adopted: the differences in the flutter mechanism between such two approaches are taken as an indicator of possible strong inaccuracies.